Advances in Microfluidics and Nanofluids - Sohel Murshed, S. M. (IntechOpen, 2021)
Microfluidics and nanofluids are rapidly growing technologies of tremendous potential and benefits. This book features a spectrum of topics on these emerging technologies that include microfluidic applications, mass production of chips, flow sensing approaches, fabrication of microfluidic channels using the micromilling process, application of micromixers for wastewater treatment and life cycle assessment, solar thermal conversion of plasmonic nanofluids, and liquid cooling, as well as carbon capture utilization and storage using nanocomposite and nanofluids. The book is intended to provide useful information and guidance to a wide variety of people including students, researchers, engineers, and manufacturers who are involved or interested in these technologies.